A hybrid bioinspired catechol-alloxazine triangular nickel complex stabilizing protons and electrons. Issue 24 (5th November 2021) - Das, Agnideep; Jobelius, Hannah; Schleinitz, Jules; Gamboa-Ramirez, Stefani; Creste, Geordie; Kervern, Gwendal; Raya, Jesus; Le Breton, Nolwenn; Guénet, Aurélie; Boubegtiten-Fezoua, Zahia; Grimaud, Laurence; Orio, Maylis; et al.
Abstract : A new class of redox-active ligands merging catechol and alloxazine structures is reported. A trimetallic triangular complex is formed upon complexation to nickel. Abstract : We report the design of a unique bioinspired ligand merging redox-active catechol and flavin-related alloxazine substructures. Upon coordination with a Ni(ii ) salt, this hybrid ligand forms a trinuclear complex containing three Ni II centers and three redox-active ligands. This air-stable metallic triangle stabilizing protons and electrons was studied by X-ray crystallography, infra -red (IR) and UV-vis spectroscopy, SQUID magnetometry (Superconducting QUantum Interference Device), MAS-NMR (Magic Angle Spinning-Nuclear Magnetic Resonance), EPR (Electron Paramagnetic Resonance), electrochemistry and DFT (Density Functional Theory). This multidisciplinary approach supports the presence of protons located on the organic ligands, and an electronic structure involving three high spin Ni(ii ) ions strongly ferromagnetically coupled with radicals. Both ligand and complex provide a new design for molecular bricks and bioinspired energy storage devices.